The Top 50 Most-Cited Shoulder Arthroscopy Studies - M. Lane Moore, B.S; Jordan R. Pollock, B.S; Kade S. McQuivey, M.D; Joshua S. Bingham, M.D (Elsevier, 2021)
Purpose: To determine the 50 most frequently cited studies in the orthopaedic shoulder arthroscopy literature and to conduct a bibliometric analysis of these studies. Methods: The Clarivate Analytics Web of Knowledge database was used to gather data and metrics using Boolean queries to capture all possible iterations of shoulder arthroscopy research. The search list was sorted so that articles were organized in descending order based on the number of citations and included or excluded based on relevance to shoulder arthroscopy. The information extracted for each article included author name, publication year, country of origin, journal name, article type, and the level of evidence. Results: For these 50 studies, the total number of citations was calculated to be 13,910, with an average of 278.2 citations per paper. The most-cited article was cited 1134 times, whereas the second- and third-most cited articles were cited 920 and 745 times, respectively. All 50 articles were published in English and came from 7 different orthopaedic journals. The United States was responsible for most of the included articles (31), followed by France (9) and Japan (3). Conclusions: The majority of the most-cited articles in shoulder arthroscopy are case series and descriptive studies originating from the United States. In addition, more than one half of the top 50 most-cited studies were published after 2004, which suggests that article age may be less important in the accumulation of citations for a rapidly growing field like shoulder arthroscopy. Clinical Relevance: The top 50 most-cited studies list will provide researchers, medical students, residents, and fellows with a foundational list of the most important and influential academic contributions to shoulder arthroscopy.